THE SELECTION OF SUSTAINABLE LOW EMISSION TECHNOLOGY IN AMMONIA PLANT USING AIM/END-USE MODEL - Nur Sajida, Gita
The ammonia industry is one of the energy-intensive, emission, and pollution industries which is responsible for high greenhouse gas (GHG) emissions. The ammonia industrial sector plays an important role in achieving Indonesia's commitment targets towards low carbon and climate-resilient development in the future. Several models have been proposed previously to quantify carbon emission. However, a separateanalysis of emissions industrial process and product use (IPPU) and from energy usage has never been done. This research uses a quantitative evaluation to analyse the mitigation effectiveness of GHG emission on the potential for energy savings, the carbon emission reduction from IPPU, and energy usage by using the AIM/end-use model during the 2010-2050 simulation year range. This year range is chosen for contribute to Long-term National Low Carbon Development Strategies 2050. AIM/End-Use model is among bottom-up model to integrate end-use energy demand and selected technological details. The model is built under the baseline scenario and several relevant mitigation scenario options, namely counter measured (CM) (i) adjusting the production process with heat recovery and replacing the catalyst (CM1 scenario), (ii) maximizing the energy efficiency of CM1 through the application of advanced technology (CM2 scenario), (iii) reducing the carbon emissions from CM2 through the application of biomass co-firing added by carbon capture and storage (CCS) (CM3 scenario). Based on the assumption, ammonia production projection in Indonesia will be 14.5 million tonnes in 2050. ACC tool at a carbon tax value of 50 USD/ton CO?e is formulated by technology option with an optimum emission reduction potential of 4.99 million tons of CO?e in the CM1, 11.91 million tons of CO?e in the CM2 scenario, and 17.17 million tons of CO?e in the CM3 scenario. Mitigation costs were USD 307.83 million, USD 690.69 million, and USD 283.58 million which were lower than each baseline of the CM1, CM2, and CM3 scenarios. The effectiveness analysis of each mitigation actions in the AIM /end-use model shows that each mitigaton scenarios driver for energy saving and GHG emissions reduction. Without mitigation, in 2050 energy intensity is 43.75 GJ/tonne of ammonia and GHG emmision intensity is 2.38 tons CO?e /ton of ammonia. Heat recovey and change the catalysts in CM1 gives a potential intensity energy saving of 37.44 GJ/tonne of ammonia and emission reduction of 2.38 tons of CO?e/tonne of ammonia. Promoting advance technologies in CM2 gives a potential intensity energy saving of 28.93 GJ/tonne of ammonia and emission reduction of 1.61 tons of CO?e/tonne of ammonia. While using biomass co-firing with CCS in CM3 gives constribution potential intensity energy saving of 41.07 GJ/tonne of ammonia and emission reduction of 1.24 tons of CO?e/tonne of ammonia. bagian ini, abstrak ditulis dalam bahasa inggris. Abstrak ditulis dengan u